2020
DOI: 10.3390/v12101105
|View full text |Cite
|
Sign up to set email alerts
|

Releasing Intracellular NS1 from Mosquito Cells for the Detection of Dengue Virus-Infected Mosquitoes

Abstract: Dengue virus (DENV), the pathogen that causes dengue fever, is mainly transmitted by Aedes aegypti. Surveillance of infected mosquitoes is a major component of integrated mosquito control methods for reducing the risk of vector-born disease outbreaks. However, a specialized rapid test for DENV detection in mosquitoes is not currently available. Utilizing immunoblotting, we found that the secretion of NS1 from both a DENV-infected mosquito cell line and mosquito bodies was below the detection threshold. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…albopictus species. Once mosquito acquired the DENV, virus would infect midgut in 3–5 days, disseminate into circulatory system to reach salivary glands in 7–10 days, and transmit virus to next host in 10–14 days 6 8 . Therefore, blocking virus acquisition or replication in the tissues of the mosquito may be a strategy for reducing the incidence of DENV transmission to humans.…”
Section: Introductionmentioning
confidence: 99%
“…albopictus species. Once mosquito acquired the DENV, virus would infect midgut in 3–5 days, disseminate into circulatory system to reach salivary glands in 7–10 days, and transmit virus to next host in 10–14 days 6 8 . Therefore, blocking virus acquisition or replication in the tissues of the mosquito may be a strategy for reducing the incidence of DENV transmission to humans.…”
Section: Introductionmentioning
confidence: 99%
“…In urban areas, the electricity can be sourced from nearby houses or streetlamps. As an additional measure for mosquito surveillance programs, captured mosquitoes from the fan-traps can be tested for dengue infection with rapid testing methods ( 40 ) to provide more information for dengue disease control, due to correlations previously identified between the number of infected mosquitoes and human dengue fever cases ( 41 , 42 ). As an additional benefit of fan-traps, previous studies have reported that dengue virus non-structural protein 1, a therapeutic target for dengue virus, can be detected from mosquitoes captured by gravid sticky traps ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, fan-traps are not hindered by retrieval issues, meaning that mosquito bodies can be obtained via air-dried conditions ( 40 , 44 , 45 ) and tested for biomarkers of dengue virus. Estimating the efficiency of fan-traps in specifically capturing gravid female mosquitoes should therefore be possible but will require further experiments.…”
Section: Discussionmentioning
confidence: 99%